Boot Camp: Preparing Teacher Candidates for the Discipline - Kristi Stuck; Amy Barlow; Gloria Flynn (The Advocate, 2018)
Colleges and universities commonly implement orientation courses to help freshmen and transfer students adjust to the academic demands and social challenges of higher education. This article examines one university’s implementation of a similar concept for teacher candidates transitioning from general to professional studies. The seminar, known as Boot Camp, is designed to prepare students for the rigor of coursework/clinical responsibilities and the teaching profession. Through a pre-post seminar questionnaire, participants showed growth in their perceptions and understandings of seminar topics. A faculty questionnaire indicated positive student outcomes from the seminar as observed through coursework and daily interactions with teacher candidates.